Stock market performance during the COVID-19 pandemic using bibliometric review / Syukriah Ali, Chaleeda Som Sak and Rosliza Md Zani - Ali, Syukriah; Som Sak, Chaleeda; Md Zani, Rosliza (UiTM Press, 2023)
This study uses bibliometric review to assess research trends, most active contributors (subject area, source titles, countries, institutions, and authors), keywords analysis, and citation analysis of publications on stock market performance during the COVID-19 pandemic. The analyses examining the 720 Scopus publications from 2020-2022 were performed using Microsoft Excel, VOSviewer, WordSift, and Harzing’s Perish or Publish. The data indicated that research trends on stock market performance rose rapidly from 2020 to 2022. China has the most articles on stock market performance during the COVID-19 pandemic. Compared to developed countries, the findings indicated that emerging countries are performing better in publications. From the expanding number of author keywords in the literature, investor sentiment, spillover effect, and uncertainty are prospective literature gaps to focus on. Future researchers and business practitioners can use the study's findings to study how unusual events affect stock market performance.